Carnitine palmitoyltransferase 1C reverses cellular senescence of MRC‐5 fibroblasts via regulating lipid accumulation and mitochondrial function. Issue 2 (6th July 2020) - Chen, Panpan; Zhang, Qianbin; Zhang, Huizhen; Gao, Yue; Zhou, Yanying; Chen, Yixin; Guan, Lihuan; Jiao, Tingying; Zhao, Yingyuan; Huang, Min; Bi, Huichang
Abstract: Cellular senescence, a state of growth arrest, is involved in various age‐related diseases. We previously found that carnitine palmitoyltransferase 1C (CPT1C) is a key regulator of cancer cell proliferation and senescence, but it is unclear whether CPT1C plays a similar role in normal cells. Therefore, this study aimed to investigate the role of CPT1C in cellular proliferation and senescence of human embryonic lung MRC‐5 fibroblasts and the involved mechanisms. The results showed that CPT1C could reverse the cellular senescence of MRC‐5 fibroblasts, as evidenced by reduced senescence‐associated β‐galactosidase activity, downregulated messenger RNA (mRNA) expression of senescence‐associated secretory phenotype factors, and enhanced bromodeoxyuridine incorporation. Lipidomics analysis further revealed that CPT1C gain‐of‐function reduced lipid accumulation and reversed abnormal metabolic reprogramming of lipids in late MRC‐5 cells. Oil Red O staining and Nile red fluorescence also indicated significant reduction of lipid accumulation after CPT1C gain‐of‐function. Consequently, CPT1C gain‐of‐function significantly reversed mitochondrial dysfunction, as evaluated by increased adenosine triphosphate synthesis and mitochondrial transmembrane potential, decreased radical oxygen species, upregulated respiratory capacity and mRNA expression of genes related to mitochondrial function. In summary, CPT1C plays a vital role in MRC‐5 cellular proliferation and can reverse MRC‐5 cellular senescence through the regulation of lipid metabolism and mitochondrial function, which supports the role of CPT1C as a novel target for intervention into cellular proliferation and senescence and suggests CPT1C as a new strategy for antiaging. Abstract : Carnitine palmitoyltransferase 1C (CPT1C) is a crucial regulator of cellular senescence via lipid metabolism and mitochondrial function in MRC‐5 cells. CPT1C knockdown leads to a lower proliferation in early MRC‐5 cells, while CPT1C gain‐of‐function decreases lipid accumulation, improves mitochondrial function, and then reverses cellular senescence of late MRC‐5 cells.